2013
DOI: 10.3168/jds.2013-6672
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting economics of using sexed semen in dairy cattle

Abstract: The use of sexed semen in the dairy industry has grown rapidly. However, high costs and low fertility have limited the use of this potentially valuable tool. This study used simulation to evaluate 160,000 combinations of key variables in 3 spheres of influence related to profit feasibility: (1) market (e.g., milk and calf prices), (2) dairy farm management (e.g., conception rates), and (3) technology (e.g., accuracy of sexing). These influential variables were used to determine the most favorable circumstances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 16 publications
3
51
2
Order By: Relevance
“…McCullock et al (2013) assessed the economic benefits of three scenarios using sexed semen on heifers alone (which have intrinsically better fertility than cows) or also including some higher genetic merit cows. They took the likely success of AI at 70% of that achievable using unsexed semen.…”
Section: Heifer Fertilitymentioning
confidence: 99%
“…McCullock et al (2013) assessed the economic benefits of three scenarios using sexed semen on heifers alone (which have intrinsically better fertility than cows) or also including some higher genetic merit cows. They took the likely success of AI at 70% of that achievable using unsexed semen.…”
Section: Heifer Fertilitymentioning
confidence: 99%
“…This provides dairy farmers with the opportunity to increase revenues from the sale of calves for meat production, by breeding the remainder of the herd with semen from beef sires (McCullock et al, 2013). Suitable beef sires would generate progeny that are easy calving with short gestation length (SGL).…”
Section: Improved Biosecuritymentioning
confidence: 99%
“…These are: (i) the price premium of sexed semen compared with conventional; and (ii) the reduction in fertility performance of sexed semen compared with conventional. A number of authors have examined the economic effects of sexed semen use in a variety of scenarios, both in year-round (Seidel, 2003;Olynk and Wolf, 2007;McCullock et al, 2013) and seasonal production systems (McMillan and Newman, 2011;Hutchinson et al, 2013a and2013b). McCullock et al (2013) described the economic advantage of using sexed semen as a function of interactions among three spheres of influence: the market environment, management practices and technological efficiency.…”
Section: Economics Of Sexed Semen Usementioning
confidence: 99%
“…With sexed semen, McCullock et al (2013) found profitability was not largely affected by added costs of sexed semen, but more so by management variables like conception rate and the market environment. Genomic engineering and gene editing are both currently afflicted with high costs and relatively poor efficiencies in producing modified, viable young.…”
Section: Economicsmentioning
confidence: 96%